OVERCOMING THE REALITY: CHALLENGES, COPING, AND INSIGHTS AMONG FRESHMEN ENGLISH MAJORS - Genivave O. Dairo; Hanna Kate F. Lazaga; Louieliza D. Yaun; Genesis G. Genelza (Galaxy International Interdisciplinary Research Journal, 2023)
This study utilized a qualitative approach, particularly phenomenological studies, to get comprehensive insights and knowledge from the chosen respondents. The seven witnesses and participants in the focus group discussion were interviewed in-depth to obtain information for the debate. We organized the availability of our members and critical sources during the general setting of the interview. This study aims to provide a broad overview of the challenges faced by first-year English majors, the coping strategies applied to address these challenges, and the insights learned along the way. By studying these students’ experiences, education professionals and institutions can gain additional insight into the specific requirements and problems of these students. This study aims to examine the different challenges these students encounter, the coping mechanisms they utilize to deal with them, and the valuable knowledge they acquire during their first year of college. As a result, first-year English majors encounter various challenges, coping mechanisms, and insights. By addressing the distinct challenges of first-year English majors, colleges and universities can establish a learning environment that fosters academic success, personal growth, and the development of first-year English primary students.